2002
DOI: 10.1055/s-2002-36357
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Activity Relationships of Flavonoids,Isolated fromScutellaria baicalensis,Binding to Benzodiazepine Site of GABAAReceptor Complex

Abstract: Twenty-six flavonoids were isolated from Scutellaria baicalensis. Their affinities for the benzodiazepine (BDZ) binding site of GABA A receptor have been studied using [ 3H]flunitrazepam binding to rat cortical membranes in vitro. The structure-activity relationships suggested that 2'-OH flavones exhibited the most potent binding affinity, which could lead to the design and discovery of new BDZ receptor ligands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…3). The presence of conjugated ketones as stated by Wang et al, (2002), and a C6-C8 00 biflavonoid linkage may have a significant role in enhanced affinities for the BZD-site.…”
Section: Hypnotic Effects Of Meoh Extract and Etoac And N-buoh Fractmentioning
confidence: 98%
“…3). The presence of conjugated ketones as stated by Wang et al, (2002), and a C6-C8 00 biflavonoid linkage may have a significant role in enhanced affinities for the BZD-site.…”
Section: Hypnotic Effects Of Meoh Extract and Etoac And N-buoh Fractmentioning
confidence: 98%
“…Flavone-glucuronides (e.g. baicalin, wogonin-7-Oglucuronide) had a low affinity for the benzodiazepine binding site (Wang et al, 2002a). The binding affinity of flavones was much higher, especially for flavones with a 2 -hydroxyl group.…”
Section: Animal and In Vitro Studiesmentioning
confidence: 99%
“…The binding affinity of flavones was much higher, especially for flavones with a 2 -hydroxyl group. Of the flavones known to occur in S. lateriflora, oroxylin A showed the highest affinity to the receptor, followed by wogonin, while baicalein was not very active (Huen et al, 2003a;Wang et al, 2002a). Hui et al (2002) investigated the anxiolytic activities of wogonin in mice and found a similar response between wogonin (7.5-30 mg/kg oral) and diazepam (1 mg/kg) in the elevated plus-maze test.…”
Section: Animal and In Vitro Studiesmentioning
confidence: 99%
“…MS-275 was synthesized according to the reported procedure [12]. The Wogon flavonoids were previously isolated in Prof. Taniguchi's laboratory [13,14].…”
Section: Chemicalsmentioning
confidence: 99%